Managing High Water Levels in Florida’s Largest Lake: Lake Okeechobee - Karl Havens (EDIS)
This 7-page fact sheet written by Karl E. Havens and published by the Florida Sea Grant College Program, UF/IFAS Extension, provides a history of Lake Okeechobee regulation schedules and an overview of the risks, constraints, and trade-offs that the US Army Corps of Engineers must consider when deciding to release flood water from the lake. http://edis.ifas.ufl.edu/sg154